Spatiotemporal Nutrient Patterns, Stoichiometry, and Eutrophication Assessment in the Tieshan Bay Coastal Water, China - Peng Zhang; Siying Wu; Menghan Xu; Xiaojun Luo; Xi Peng; Chaoxing Ren; Jibiao Zhang (Journal of Marine Science and Engineering, 2023)
Land-source inputs into coastal water have increased remarkably in recent years, resulting in the deterioration of water quality, eutrophication, and algae blooms. However, we have limited understanding of spatiotemporal nutrient patterns, stoichiometry, and eutrophication assessment in Tieshan Bay coastal water at present. To investigate the rapid development of the coastal areas in Tieshan Bay in the South China Sea, nutrients and other physicochemical parameters were observed in Tieshan Bay during the normal season (April), wet season (July), and dry season (October) in 2021. The results showed that the average concentrations of dissolved inorganic nitrogen (DIN), dissolved inorganic phosphorus (DIP), and chemical oxygen demand (COD) in Tieshan Bay are 0.071 ± 0.115 mg/L, 0.008 ± 0.013 mg/L, and 0.71 ± 0.219 mg/L, respectively. DIN/DIP ratio ranges from 9.1–69.3, with an average value of 19.9 ± 19.2, which exceeds the Redfield value, behaving P limitations. In addition, the mean eutrophication index (EI) was low in Tieshan Bay, with an average value of 0.5 ± 1.5. Moreover, the hotspot coastal water with high DIN, DIP, and COD concentrations was located in the upper half of Tieshan Bay in all seasons. In addition to the DIN, DIP, and COD contributions to EI, the average contribution rates of DIN, DIP, and COD are 26.6%, 8.8%, and 64.6%, respectively, which leads to the largest contribution of COD to EI. Furthermore, the average comprehensive index (CI) of organic pollution in Tieshan Bay surface seawater ranged from −1 to 5.6. The seawater near Hepu in S8 station has organic pollution in wet and dry seasons, and Tieshan Bay’s middle region also has slight organic pollution. Additionally, the DIN, DIP, and COD had significant relationships with salinity (p < 0.05), suggesting that coastal water quality is affected by land-based sources input. To achieve the seawater quality target and mitigate regional eutrophication, it is critical to implement land-based source management across the river-bay-coastal water continuum.